Potential Legal Conflict For The Implementation Of Financial Services Authority Regulation Number 65 /POJK.04/2020 - Theresia Anita Christiani (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2021)
Financial Services Authority Regulation Number 65 / POJK .04 / 2020 was promulgated to increase effectiveness and justice in law enforcement in the capital market sector. The form of legal protection regulated is the Return of Unauthorized Profits and the Investor Loss Compensation Fund (Disgorgement Fund). The research objective in this paper is to find potential legal conflicts that arise in the implementation of the Financial Services Authority Regulation Number 65 / POJK .04 / 2020. The research method, this type of research is normative juridical research, which uses secondary data. The findings obtained are that there are two potential legal conflicts. First, there is a potential conflict between the Financial Services Authority Regulation Number 65 / POJK .04 / 2020 and Law Number 37 of 2004. Second, the Potential Conflict between the Financial Services Authority Regulation Number 65 / POJK. 04/2020 with Law Number 37 the Year 2004 and Law Number 40 the Year 2007, which will obstruct legal objectives.